Front Cover: The Disordered Landscape of the 20S Proteasome Substrates Reveals Tight Association with Phase Separated Granules. Issue 21 (19th November 2018) - Myers, Nadav; Olender, Tsviya; Savidor, Alon; Levin, Yishai; Reuven, Nina; Shaul, Yosef
Abstract : DOI:10.1002/pmic.201800076 In article number1800076, Myers et al. report that many proteins can be degraded by the 20S Proteasome complex. RNA binding intrinsically disordered proteins (IDPs), which form phase–separated granules within the cell, are a large subset of these substrates. These proteins in addition to harboring an RNA binding domain (RBD) are enriched with prion like domains (PrLD) and low complexity domains (LCD) revealing a novel link between phase separation and 20S degradation. A small group of these proteins which are implicated in ALS disease are the most preferential 20S substrates.